New cooling system for a three-axis multi-anvil press with 6-6 geometry. Issue 2 (3rd April 2021) - Howard, Christopher M.; Walte, Nicolas P.
ABSTRACT: A new custom-designed cooling system is described that was developed for the SAPHiR three-axis multi-anvil press with MA6-6 anvil geometry at the FRM II neutron source in Garching. The system was designed to remove heat from the secondary anvils by flowing a cryogen around custom-designed cooling rings or cooling jackets. Currently, this cryo-system is capable of achieving temperatures of 83 K without interfering with the anvil geometry and pressure transfer, thus not limiting the attainable maximum pressure or the capability of performing deformation experiments. In this study, pressures of up to ca. 8 GPa were attained at 83 K with sample volumes up to 130 mm 3 . The system is portable and can be implemented into any three-axis multi-anvil press with a MA6-6 anvil geometry, opening up new areas of high pressure cryo-research at synchrotron and neutron facilities, including investigating the interior of icy moons.